2017
DOI: 10.1021/acsbiomaterials.6b00723
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanics on FGF-2 and Heparin Reveal Slip Bond Characteristics with pH Dependency

Abstract: Fibroblast growth factor 2 (FGF-2) -an important paracrine growth factor -binds electrostatically with low micro-molar affinity to heparan sulphates present on extracellular matrix proteins. A single molecular analysis served as a basis to decipher the nanomechanical mechanism of the interaction between FGF-2 and the heparan sulphate surrogate -heparin -with a modular atomic force microscope (AFM) design combining magnetic actuators with force measurements at the low force regime (10 1 -10 4 pN/s). Unbinding e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…The lifetime values are consistent with the responses in neurons (e.g., neurite retraction) triggered by the astrocyte proteins: α V β 3 integrin induces a significant retraction of neuronal processes, while the proteoglycan Syndecan-4 does not promote any morphological changes ( Figure 2D ). The slip bond behavior found for both bi-molecular interactions coincides with the mechanical characterization described for Thy-1–α 5 β 1 binding ( Fiore et al, 2014 ) as well as for FGF with the HSPG ( Sevim et al, 2017 ). Moreover, we found that the ternary complex (Thy-1–α V β 3 integrin + Syndecan-4) is more stable in terms of force-dependent lifetime than each binary complex.…”
Section: Discussionsupporting
confidence: 79%
“…The lifetime values are consistent with the responses in neurons (e.g., neurite retraction) triggered by the astrocyte proteins: α V β 3 integrin induces a significant retraction of neuronal processes, while the proteoglycan Syndecan-4 does not promote any morphological changes ( Figure 2D ). The slip bond behavior found for both bi-molecular interactions coincides with the mechanical characterization described for Thy-1–α 5 β 1 binding ( Fiore et al, 2014 ) as well as for FGF with the HSPG ( Sevim et al, 2017 ). Moreover, we found that the ternary complex (Thy-1–α V β 3 integrin + Syndecan-4) is more stable in terms of force-dependent lifetime than each binary complex.…”
Section: Discussionsupporting
confidence: 79%
“…Specifically, we use atomic force microscopy (AFM) based single-molecule force spectroscopy (SMFS) to quantify the response of individual molecular interactions to tensile forces. This force probe technique is now well established for the analysis of intra- and intermolecular forces (29, 30) and is emerging for the probing of glycosaminoglycan-protein interactions (16, 31, 32). A prerequisite of AFM SMFS measurements is the proper immobilization of the molecules to be probed, in a way that permits the controlled application of the necessary tensile forces.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing ks H by four orders of magnitude only decreased cell surface HSPG concentration by about two times. Finally, it has recently been proposed that FGF2 and heparin demonstrate slip-bond characteristics 21 . We therefore varied FGF2-HSPG k off several orders of magnitude above and below the base value (dotted line, Figure 4E).…”
Section: Resultsmentioning
confidence: 99%
“…Computational studies of the endothelial glycocalyx have suggested that shear stress stretches cell surface HSPG [60][61][62] , which would expose additional FGF2 binding sites and increase FGF2 capture by HSPG as FGF2 dimers in flow. Sevim et al investigated the nanomechanics of the FGF2-HSPG bond itself using atomic force microscopy 21 . Their data suggest that FGF2-HSPG dissociation rate was constant at loading rates of 101 to 106 pN/s but then increased approximately 4500 times at higher loading rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation